Caregivers' Preferences of COVID-19 Vaccination for Children: A Cross-sectional Study From Rural South India - U.C SAMUDYATHA; Bhavyashree BALAJI; Meghna SINGH; Megha GOWDA (Medeniyet Medical Journal)
Objective: This study aimed to document caregivers' perceptions and preferences regarding coronavirus disease-19 (COVID-19) vaccination among children. Methods: This cross-sectional study analyzed 272 caregivers with 347 children (aged 1-18 years) attending a subdistrict rural hospital in February-March 2022. Results: Vaccine acceptance was high (93.4%). Although fear of side effects was the most common reason not to vaccinate, a higher proportion of caregivers willing to vaccinate children had consulted healthcare personnel to clarify queries related to side effects. Familiar vaccination sites, where children had previously received routine immunization (RI), such as government hospitals, and Anganwadis (community-based childcare centers) where vaccines were available free of cost on all working days, were the most preferred for COVID-19 vaccination, followed by schools. Only 5.5% of the caregivers preferred private hospitals. Vaccination at home was desired for chronically ill and out-of-school children. RI as per age was associated with the willingness to vaccinate. In addition to protection from COVID-19, other benefits identified by willing parents were being able to attend schools, recreation, and travel. Conclusions: Out-of-school children, children left or missed out in RI, and children with chronic illness can be at risk of being left out for COVID-19 vaccination and can be included by expanding vaccination services house-to-house as in adults. Media engagement and communication must be interactive to address issues, such as fear of side effects, and promote additional benefits of vaccination.